GE_GERICHTE C/23466/2016 vom 5. Oktober 2017 - GE Cour de justice (2017)
BAIL À LOYER ; LOYER INITIAL ; AUGMENTATION(EN GÉNÉRAL) ; FORMULE OFFICIELLE | LDTR.10.al1; LDT.12; CO.253; CO.1; CO.270.al2; OBLF.19